Acquisition of non-canonical word orders in Mandarin Chinese - Ji, Yue; Sheng, Li; Zheng, Li (Frontiers in Psychology, 2023)
To better understand Mandarin-speaking children’s acquisition of non-canonical word orders, we tested comprehension and production of Mandarin non-canonical active ba-construction, passive bei-construction, in comparison with canonical active SVO sentences among 180 children between three and six years of age. Our results showed that children had more difficulties with bei-construction compared to SVO sentences in both comprehension and production, but early problems of ba-construction only lied in production. We discussed these patterns in connection with two accounts of language acquisition which attribute language development to the maturation of grammar or to the exposure to the input respectively.